Problematika Pemaknaan Istilah Pendidikan Islam dalam Perspektif Semantik Arab - Janah, Nyai Raodotul; Ali, Moh; Arifudin, Iis (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This research aims to analyze the semantic meanings of three key terms: al-tarbiyah al-islāmiyyah, al-ta'līm al-islāmī, and al-ta'dīb al-islāmī from an Arabic linguistic perspective. Using the qualitative library research method, the research data focuses on the semantic interpretation of Islamic education terminology through classical Islamic literature, contemporary scholarly works, authoritative Arabic dictionaries, and academic journals. The data collection technique employs systematic documentation by identifying, inventorying, classifying, and thoroughly reading relevant sources to extract etymological information, morphological patterns, and contextual usage. Data analysis uses content analysis with a descriptive-comparative semantic approach through data reduction, systematic presentation based on semantic categories, and conclusion drawing with source triangulation. The findings reveal that al-tarbiyah derives from the root rabbā emphasizing holistic nurturing with divine dimension, al-ta'līm from 'alima focusing on cognitive knowledge transfer, and al-ta'dīb from addaba prioritizing character formation and moral internalization. Each term carries a distinct philosophical orientation and educational scope that should determine the paradigm, curriculum, methodology, and evaluation of Islamic education. The research identifies that semantic confusion occurs due to limited semantic studies, the influence of Western literature translations, and weak terminology standardization in Indonesian Islamic educational institutions. Institutions often use these terms interchangeably without understanding their substantial differences, leading to misalignment between nomenclature and educational practice. This study recommends conceptual reconstruction and consistent implementation based on a clear understanding of semantic meanings to optimize Islamic education effectiveness.